Novel cytokine marker available for skin irritation testing of medical devices using reconstructed human epidermis models. (October 2020) - Kato, Reiko; Miyajima, Atsuko; Komoriya, Kaoru; Haishima, Yuji
Abstract: In biological safety evaluation of medical devices, false-negative results have been observed during skin irritation testing using the reconstructed human epidermis (RhE) model when measuring cell viability as a single marker. Therefore, to improve testing accuracy, this study conducted a comprehensive survey and performance evaluation of cytokines to identify a second marker. In addition to IL-1α, macrophage migration inhibitory factor (MIF) was newly identified as a candidate marker, in the Bio-Plex assay of EpiDerm model exposed to polymer sample extracts. Irritation based on cell viability level was not accurately determined in LabCyte model using silicone spiked with 25% heptanoic acid (HA). By contrast, the irritation potency was accurately assessed in detail by measuring IL-1α or MIF. Further, IL-1α and MIF levels in EpiDerm, LabCyte, and EpiSkin models stimulated with sodium dodecyl sulfate (SDS) were inversely correlated with cell viability, and were detected even at low SDS concentrations without cell toxicity. Additionally, MIF demonstrated greater S/N ratio and dose-dependency at high SDS concentrations in some models compared to IL-1α. These results indicated that MIF might be a useful second marker for improving the sensitivity and accuracy of skin irritation testing with RhE models. Highlights: MIF is a novel cytokine marker for skin irritation testing using RhE models of medical devices. Measuring MIF in addition to cell viability may improve the sensitivity and accuracy of irritation testing using RhE models. LabCyte model can effectively detect irritation potency of medical device extracts.